Strategi Komunikasi Pengelola Prodi KPI dalam Menciptakan Iklim Organisasi yang Kondusif - Bakti Komalasari (Jurnal Dakwah dan Komunikasi, 2016)
An Islamic broadcasting and comunication study is one of the oldest programs in STAIN Curup. As the oldest Program, Many challenged have been faced by it. One thing became an urgent is organization culture which is influenced by the culture of communication strategies in Prodi KPI. For thet matter, the problem of communication strategy becomes very essential considering that communication strategy also have an impact on job satisfactions of individuals who take shelter under the organization/institution. There are two things might be cause people are nort satisfied with this job. Firstly, because incase the person does not get the information needed to perform their jobs. Secondly, the relationship with partner in jobs does not run well ot in other words job satisfication is related to communication problems.